Konseling Pastoral Dengan Teknik Cognitive Restructuring pada Remaja yang Melakukan Percobaan Bunuh Diri - Rima Angelina; Yelinda Sri Silvia; Herman Titting (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
In this transition period adolescents are faced with various life challenges both from within themselves and from their environment, in facing these challenges not all teenagers are able to overcome them alone, the inability to face problems often leads teenagers to solve problems with suicidal solutions, so it is necessary to do something about it. youth-specific approach. The purpose of this study was to find out how pastoral counseling attempts with cognitive restructuring on adolescent suicide attempts. This research was conducted with a qualitative method with the type of social descriptive research. The result of this research is that in conducting pastoral counseling, the behavior of adolescent suicide attempts can be carried out with seven stages of pastoral counseling, namely; building relationships, history taking, diagnosis, treatment planning. treatmentt, evaluation and review and termination. This study uses one counseling technique that focuses on the mind, namely the cognitive restructuring. The implementation of pastoral counseling for adolescents who have attempted suicide can go through the seven stages above and focus on questions based on cognitive restructuring so that it can be formulated that pastoral counseling with cognitive restructuring is achieved if adolescents can map their minds, open up, and have good goals in life.